Study on the Cutter–Granite Interaction Mechanism in High-Temperature Geothermal Wells - Yang, Yan; Song, Dongdong; Huang, Kuilin; Ren, Haitao; Yang, Yingxin; Qiu, Shunzuo; Huang, Zequan (Energies (Basel), 2025)
In high-temperature geothermal wells, the formation usually has extremely high abrasiveness, hardness, and temperature, which pose severe challenges to drilling tools. Among them, the interaction between the cutter of the drill bit and the rock is the key factor determining the rock-breaking efficiency of PDC (Polycrystalline Diamond Composite) drill bits. To further explore the rock-breaking mechanism of cutters on granite, this study adopts a combination of experimental and simulation methods to conduct systematic research. The results indicate that the specific crushing work increases and then decreases with rising temperature, reaching a minimum of 0.388 J/mm3 at 200 °C. In the temperature range of 300 °C to 500 °C, the specific crushing work is 15% lower than at room temperature. The specific crushing work during instant cooling is 12–25% lower than that during self-cooling, with instant cooling showing higher rock-breaking efficiency. As the rake angle increases, the specific crushing work initially decreases and then increases. The smallest specific crushing work, 0.383 J/mm3, occurs at a rake angle of 10°, where the number of debris and particle size are maximized. With deeper cutting depths, the specific crushing work gradually decreases, resulting in more debris, larger particle sizes, and higher cutter surface temperatures. These findings clarify the variation laws of rock load, cutting tooth distribution, and rock fragmentation state when the PDC bit breaks rocks. A rake angle of 10° can be used as the selection of cutting tooth inclination angle for PDC bit design, providing a theoretical basis for the design and application of PDC bits in high-temperature geothermal drilling and holding significant guiding importance. Considering that increasing the depth of penetration can cause uneven wear of the cutter, the drilling parameters can be controlled under certain conditions to achieve a penetration depth of 2 mm, thereby improving the rock-breaking efficiency and working life of the PDC bit.